Inculcating leadership skills through Mahallah leadership training (McLEAD 2015) - Omar, Muhamad Fuzi; Othman, Muhammad Hanif; Mohd Yusof, Danial; Mohd. Shariff, Ros Aniza (Contemporary Research Center Australia, 2015)
The purpose of this paper is to explain the nature of the Mahallah Leadership Programme (McLead) as a means to inculcate the leadership values to the student leaders at International Islamic University, Malaysia. The analysis was done based on the progrmme which was conducted at Akademi Pembangunan Belia, Batu Gajah Perak on February 6 to 8, 2015. About 192 Mahallah representative committees from all Gombak Mahallat participated in the programme. However, only 162 participants gave their feedbacks for the programme. Several analyses were conducted based on their feedback to the programme. The results shows that there are three major reasons why the students are interested to be members of MRC; opportunity to conduct programme; ability to polish their leadership skills and lastly to develop their potential as leaders at higher levels. In another analysis the students also expressed their satisfactions with the conduct of the programme. Lastly the analysis also identified the major skills acquired by the students throughout the activities of the programme.